Do early neutrophil to eosinophil ratio and the levels of neutrophil and white blood cells predict intra-hospital mortality in patients with spontaneous intracerebral hemorrhages? - Özeren, Ersin; Güneş, Muzaffer (Journal of Surgery and Medicine, 2020)
Aim: In recent years, inflammatory markers such as red blood cell distribution width (RDW), neutrophil to lymphocyte ratio (NLR), and C-reactive protein to albumin ratio (CAR) have been investigated in spontaneous intracerebral hemorrhage (ICH). However, they were not analyzed together in ICH. In the present study, we examined whether neutrophil, neutrophil to eosinophil ratio (NER), and white blood cell (WBC) levels along with the above-mentioned markers predict the intrahospital mortality in patients diagnosed with spontaneous ICH at admission. Methods: We conducted this retrospective cohort study by examining spontaneous ICH patients hospitalized in our clinic between April 2015 and March 2019. We divided patients into two groups, as survivors and non-survivors. The receiver operating characteristics (ROC) curve analysis test was used to evaluate the predictive value of laboratory variables for mortality and to calculate cut-off values. Results: A total of 130 patients, 82 survivors and 48 non-survivors, were included in the study. The patients who were non-survivors at the hospital had significantly higher median hemorrhage volume, WBC, and neutrophil levels compared to those of survivors (P<0.001, P=0.001 and P=0.003, respectively). There was no significant difference between the two groups in terms of median CAR, NLR, NER, and RDW-SD values (P=0.216, P=0.237, P=0.229, and P=0.215, respectively). The area under the ROC curve was 0.676 (95% CI, 0.57-0.78) for WBC and 0.659 (95% CI, 0.56-0.76) for neutrophil. Conclusion: Our results showed that the elevated neutrophil and WBC levels at the acute phase of spontaneous ICH predict the intrahospital mortality of the patients. Further studies are required for the predictive value of NER.